2018
DOI: 10.1073/pnas.1716164115
|View full text |Cite
|
Sign up to set email alerts
|

Widespread changes in transcriptome profile of human mesenchymal stem cells induced by two-dimensional nanosilicates

Abstract: SignificanceWe demonstrate the use of next-generation sequencing technology (RNA-seq) to understand the effect of a two-dimensional nanomaterial on human stem cells at the whole-transcriptome level. Our results identify more than 4,000 genes that are significantly affected, and several biophysical and biochemical pathways are triggered by nanoparticle treatment. We expect that this systematic approach to understand widespread changes in gene expression due to nanomaterial exposure is key to develop new bioacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
146
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 134 publications
(167 citation statements)
references
References 58 publications
8
146
1
Order By: Relevance
“…A recent study has shown that after mixing nanoclay with cell culture media containing serum, a significant increase in hydrodynamic diameter (D H ) from ~45 nm to ~90 nm and a decrease in zeta potential () from -40 mV to -25 mV are observed. [13] These results indicate that serum protein is physically adsorbed on nanoclay surface via electrostatic interactions. The adsorption of protein onto nanoparticle surfaces dictate nanoparticle-cellular interactions.…”
Section: Interactions Of Laponite® Nanoclay With Proteinsmentioning
confidence: 83%
See 2 more Smart Citations
“…A recent study has shown that after mixing nanoclay with cell culture media containing serum, a significant increase in hydrodynamic diameter (D H ) from ~45 nm to ~90 nm and a decrease in zeta potential () from -40 mV to -25 mV are observed. [13] These results indicate that serum protein is physically adsorbed on nanoclay surface via electrostatic interactions. The adsorption of protein onto nanoparticle surfaces dictate nanoparticle-cellular interactions.…”
Section: Interactions Of Laponite® Nanoclay With Proteinsmentioning
confidence: 83%
“…Transmission electron microscopy images have shown diameter of individual nanoclay ~20-50 nm and atomic force microscopy have shown a thickness of 1-2 nm (Fig 2b). [13] Due to random thermal motions of the nanoclay and charge distribution, the individual nanoclay sheets begin to orient in an edge-to-face arrangement that allows for faster exfoliation. Increased nanoclay concentrations exfoliate faster due to the formation of a macroscopic network that holds the individual sheet in position with electrostatic forces, while the tactoid exfoliates.…”
Section: Exfoliation Of Nanoclaymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many efforts have demonstrated that novel degradable 2D nanomaterials especially nanoclay particles and black phosphorus (BP) nanosheets with excellent bioactivity could induce osteogenic differentiation of stem cells . The innate osteoinductive performance of nanoclay were attributed to both biophysical properties (size, physical shape, and surface charge) and biochemical signaling (mineral ions dissolution products) of the nanomaterials, whereas the remarkable osteoinduction capability of BP were mainly mediated by in situ phosphorus driven, calcium‐extracted mineralized extracellular matrix during the process of BP degradation .…”
Section: Introductionmentioning
confidence: 99%
“…Whole transcriptome analysis using RNA-sequencing (RNA-Seq) is an effective approach to uncover changes in gene expression and molecular processes that might be impacted by NP exposures, [14][15][16][17][18][19][20] including exposures to low or subtoxic NP concentrations. [14][15][16] Recent work found human lung cells exposed to a non-cytotoxic dose of TiO 2 NPs for 24 h resulted in over 2000 differentially expressed genes as compared to unexposed cells.…”
Section: Introductionmentioning
confidence: 99%